2009
DOI: 10.1002/dc.21130
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic detection of Stronyloides stercoralis in a 55‐year‐old Hispanic man with routine rectal/anal pap smear

Abstract: The anal-rectal cytology is introduced recently to evaluate human-papillomavirus related cellular changes in the cells of anal canal. It is especially useful in high risk patients such as HIV patients. Very few reports were published regarding cytomorphological findings in anal cytology. Strongyloides stercoralis is an enteric helminthic parasite with particular significance in immunocompromised patients. The infection is asymptomatic or manifests as mild gastrointestinal symptoms in normal hosts. The infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…To our knowledge, this is the first report of Giardia intestinalis identified in an anal PAP. Zhou et al recently reported the incidental detection of the helminth Strongyloides stercoralis on routine cytologic examination of an anal PAP in an HIV‐positive male 5. As the anal PAP is increasingly adopted as a screening measure for squamous cell abnormalities, the number of gastrointestinal organisms detected is likely to increase.…”
mentioning
confidence: 99%
“…To our knowledge, this is the first report of Giardia intestinalis identified in an anal PAP. Zhou et al recently reported the incidental detection of the helminth Strongyloides stercoralis on routine cytologic examination of an anal PAP in an HIV‐positive male 5. As the anal PAP is increasingly adopted as a screening measure for squamous cell abnormalities, the number of gastrointestinal organisms detected is likely to increase.…”
mentioning
confidence: 99%
“…The vegetable and fruit contaminants can pose a diagnostic challenge by mimicking microorganisms, viral changes, or malignant cells. There are a few papers illustrating the basic characteristics of vegetable contaminants, but none has systematically described the morphology of fruits [1][2][3][4][5][6]. In this paper, we describe some of the basic identifying characteristics of fruits and expand upon a more comprehensive list of vegetables.…”
Section: Introductionmentioning
confidence: 99%